Odpowiedzi

Najlepsza Odpowiedź!
2010-02-18T19:54:21+01:00
2x-3y=10 / *(-5)
5x+5y=0 / *2

-10x+15y = -50
10x+10y = 0 dodajemy stronami i x sie skraca

25y = -50 / :25
y = -2 podstawiamy do pierwszego równania

2x-3y = 10
2x - 3* (-2) = 10
2x +6 = 10
2x = 10-6
2x = 4 /:2
x = 2

x=2
y=-2
2010-02-18T19:56:00+01:00
2x-3y=10
5x+5y=0/:5

2x-3y=10
x+y=0/×(-2)

2x-3y=10
-2x-2y=0

-5y=10
y=10:-5
y=-2

x=-y
x=2

odp. x=2
y=-2
2010-02-18T19:57:48+01:00
2x-3y=10/*5
5x+5y=0/*3

10x-15y=50
15x+15y=0

25x=50/25
x=2

2x-3y=10/*5
5x+5y=0/*(-2)

10x-15y=50
-10x-10y=0

-25y=50/(-25)
y=-2